Desmoplastic Small Round Cell Tumor Is an Important Mimic of High-Grade Carcinoma in Colonic Biopsy Samples. Issue 2 (March 2022) - Hissong, Erika; Yantiss, Rhonda K.
Abstract: Desmoplastic small round cell tumor (DSRCT) is a rare but aggressive malignancy that usually occurs within the intra-abdominal cavities of young adult males. Most DSRCTs can be reliably diagnosed based on the presence of characteristic morphology; coexpression of epithelial, myogenic, and neural markers; and detection of the reciprocal translocation t(11;22)(p13:21) associated with the EWS::WT1 fusion. However, occasional tumors lack classic features, affect older adults, or are located outside the abdominal cavity. Mucosal biopsy samples can pose challenges when both the stromal and epithelial components are not represented. Herein, we present a case of DSRCT that simulated clinical and histologic features of a colonic adenocarcinoma. Biopsy sampling revealed nests of cytokeratin-positive epithelioid cells that simulated a high-grade carcinoma with neuroendocrine features. This case report emphasizes the importance of considering this rare entity when presented with high-grade epithelioid tumors that occur in young patients.